2003
DOI: 10.1161/01.hyp.0000102862.93418.ee
|View full text |Cite
|
Sign up to set email alerts
|

Neither Perceived Job Stress Nor Individual Cardiovascular Reactivity Predict High Blood Pressure

Abstract: Abstract-We have reported that high job strain was associated with a significantly higher diastolic blood pressure (DBP) of 4.5 mm Hg during the working hours, irrespective of BP reactivity to a stress test. We report the final results of the first 5-year follow-up study, which aimed to assess the respective influences of perception of professional strain and cardiovascular reactivity to a mental stress test on BP. A cohort of 292 healthy subjects (meanϮSEM age, 38Ϯ1 years) was followed up for progression to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 26 publications
0
48
0
1
Order By: Relevance
“…Although some researchers have found an association between job strain and the development of hypertension in longitudinal studies, 42 others have not found such an association. 41 Our results show that high job strain is associated with increased BP reactivity to an alpha agonist. This supports the results of a study conducted by Steptoe et al 43 in which individuals with high job strain had greater BP reactivity to behavioral stress than those with low job strain.…”
Section: Discussionmentioning
confidence: 53%
“…Although some researchers have found an association between job strain and the development of hypertension in longitudinal studies, 42 others have not found such an association. 41 Our results show that high job strain is associated with increased BP reactivity to an alpha agonist. This supports the results of a study conducted by Steptoe et al 43 in which individuals with high job strain had greater BP reactivity to behavioral stress than those with low job strain.…”
Section: Discussionmentioning
confidence: 53%
“…Number of studies reporting a statistically significant deleterious effect / total number of studies having these methodological characteristics (reference number) reporting a deleterious effect of the demand-control-support factors on blood pressure according to study designs (cross-sectional, prospective or case-control), blood pressure (BP) measurements (office or ambulatory), and outcome (hypertension or BP level). (23,142,148,154) 0 / 1 (137) 1 (163) /1 (163) 1 (167) (142,148,161,180) 4 (155,166,176,182) / 5 (137,155,166,176,182) 0 /0 1 (167) / 1 (167) 21 / 40 a Studies on both BP level and hypertension (137,147,158,162,167). b Two studies also reported a significant protective effect of job strain (131,157).…”
Section: Studies On Eri Modelmentioning
confidence: 99%
“…However, creating prospective cohorts free of the outcome under study at baseline is an important methodological quality since it allows causal inferences to be made by ensuring that the exposure precedes the outcome. In keeping this rationale, most prospective studies on hypertension (4/6 studies) opted to exclude hypertensive workers at baseline (137,142,154,191) …”
Section: Selection Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Hypertension is now a burden to the society and several modifiable risk factors contribute directly to this burden. 4 High job strain has been associated with significantly higher diastolic blood pressure of 4.5mmHg during working hours 5 and it has been proven that chefs showed one risk factor more than office workers. 6 There is also a dearth of information on diet related chronic diseases in West Africa creating a challenge for comparative research for intervention purposes.…”
Section: Introductionmentioning
confidence: 99%